Financial contagion and the wealth effect: An experimental study - Anna Bayona; Oana Peia (University College Dublin, UCD Centre for Economic Research, 2020)
We design a laboratory experiment to test the importance of wealth as a channel for financial contagion across markets with unrelated fundamentals. Specifically, in a sequential global game, we analyze the decisions of a group of investors that hold assets in two markets. We consider two treatments that vary the level of diversification of these assets across markets, which allows us to disentangle the wealth effect from other sources of financial contagion. We provide evidence of contagion due to a wealth effect when investors have completely diversified portfolios. In this treatment, for certain ranges of fundamentals, we show that a coordination failure in the first market reduces investors' wealth, which makes them more likely to withdraw their investments in the second market, thereby increasing the probability of a crisis.
Keywords: C72; C92; D8; G01; G11; 330; Financial contagion; financial crises; wealth; coordination games; global games